EFA and CFA analysis: Development and validation of a test instrument for mathematical abstraction skills - Dwi Rismi Ocy; Iva Sarifah; Riyadi Riyadi (Journal of Research and Advances in Mathematics Education)
Mathematical abstraction skills are fundamental for advanced reasoning and problem-solving; however, assessing these skills in senior high school students poses challenges due to the limited availability of validated instruments. This study aims to develop and validate a test instrument for measuring mathematical abstraction skills in Indonesian high school students. The instrument targets three hierarchical cognitive levels: perceptual abstraction, internalization, and interiorization. A quantitative approach was used, involving Exploratory and Confirmatory Factor Analysis (EFA and CFA) to establish construct validity. Content validity was first evaluated by 17 mathematics educators using Aiken’s V index, followed by expert judgment from five specialists. A field test with 507 students provided the dataset for analysis. Findings from EFA and CFA confirmed that the instrument exhibited strong construct validity and reliability, with clear alignment between items and the targeted abstraction levels. The internal consistency metrics demonstrated the instrument’s ability to reliably assess mathematical abstraction across cognitive hierarchies. This validated tool contributes to mathematics education by providing a reliable means for assessing abstraction skills, facilitating improvements in instructional strategies and student evaluations. Its potential applications extend to educational research and classroom assessments, offering educators insights into students’ reasoning processes to support deeper learning outcomes.